Do extended transport times and rest periods impact on eating quality of beef carcasses?. (June 2018) - Polkinghorne, Rod; Philpott, Judy; Thompson, J.M.
Abstract: The experiment tested the effect of four extended transport treatments on sensory and objective meat quality in beef. A total of 343 steers (88 steers from each of three properties and 79 from a fourth property) were allocated to four treatments including a 12 hour transport time (T12), 24 hour transport time (T24), 24 h as 12 hour transport time, a 12 hour rest, with a further 12 hour transport (T12 ~ T12), 36 hour transport treatment (T36). Within property departure times of treatments were staggered to arrive at the abattoir together. There were no significant transport effects ( P  > .05) on live animal, carcass traits, consumer sensory scores, and objective meat quality of the longissimus lumborum . There was large between property variation in the proportions of carcasses excluded from grading on the basis of low ribfat, high ultimate pH and dark meat color scores. Variation in these traits was not associated with transport treatments and was likely related to variation in on-farm factors.